Radioisotope excited X-ray fluorescence analysis of Asellus Aquaticus (Crustacea: Isopoda) from Istanbul as an indicator of environmental metal pollution - Erkan, B. M.; Bassari, A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (My University, 2001)
Some metal contents of the freshwater isopod: Asellus aquaticus (Crustacea: Isopoda), collected from the pool of the botanical garden of Istanbul University (at the vicinity of old city center of Istanbul), were analysed, in order to investigate urban metal pollution. The analysis of the homogenized sample of isopods indicated that it contained K, Ca, Mn, Fe, Cu, Ni, Zn, Pb, Br, Rb, Sr, Y, Zr, Ba, Cd, Cs and Hg in different amounts. The results were compared with those of other isopods and various organisms.